Analisis Faktor Penyebab Sengketa Tanah dan Implikasinya terhadap Hak Para Pihak di Kecamatan Insana Utara, Kabupaten Timor Tengah Utara - Lidia Anjelina Laos; Sukardan Aloysius; Agustinus Hedewata (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The purpose of this writing is to determine the factors that cause land disputes and their implications for the rights of the parties in North Insana District, North Central Timor Regency and to determine the legal consequences for the rights of parties in land disputes in North Insana District, North Central Timor Regency. The benefit of this research is as information material to increase insight and knowledge regarding the title of the thesis which the author will research and will be useful for scientific material, especially land disputes in the civil law specialization. The method used in this research is an empirical legal research method. The results of this research show (1) The factor that caused the land dispute that occurred in North Insana District was the factor of personal conflict of interest, namely that the defendants grabbed the land, occupied and cultivated the land based on their personal interests without paying attention to the ownership of the land so that causing land disputes. (2) The consequence of the land dispute is that the owner suffers losses both material and immaterial, so that the defendant is given sanctions in the form of a fine. The conclusions of this research are (1) The factor that causes land disputes that occur in North Insana District is the factor of conflict of personal interest by taking over for personal gain. (2) The consequence of the land dispute is that the owner suffers losses, so that the dispute party receives sanctions in the form of fines to be given to the owner. The author's suggestion is that the Village Head as a mediator must bring the two parties together to make peace so that social relations between the two parties can return to running well.